Testing of Draw- and Buffing Gear Components on Dynamic Test Stand at the Faculty of Transport Engineering of the University of Pardubice (Current Problems in Rail Vehicles, 2021)
This contribution deals with tests of components of draw- and buffing gear of railway vehicles realized at the Faculty of Transport Engineering of the University of Pardubice, especially in framework of student’s projects and theses. In the beginning, the attention is paid to the tests of dynamic characteristics of elastomer suspension components of draw gears and buffers. The tests were performed in order to create a mathematical model of these components for application in multi-body simulations for investigation of longitudinal train dynamics effects, because a description of these components only by their static characteristics seems to beinsufficient in certain situations. Besides to that, a preparation of tensometric screw coupling for measurement of traction forces is introduced in the paper. This measuring device will be applied especially in further research of running resistance of railway vehicles as well as at the experimental verification of results of the longitudinal train dynamics simulations.
Keywords: railway vehicle; buffer; draw gear; screw coupling; elastomer spring; characteristics; dynamic test stand; longitudinal train dynamics; multi-body simulation; train running resistance